2015
DOI: 10.3390/en8087968
|View full text |Cite
|
Sign up to set email alerts
|

Release of Extracellular Polymeric Substance and Disintegration of Anaerobic Granular Sludge under Reduced Sulfur Compounds-Rich Conditions

Abstract: Abstract:The effect of reduced form of sulfur compounds on granular sludge was investigated. Significant release of extracellular polymeric substance (EPS) from the granular sludge occurred in the presence of sulfide and methanethiol according to various concentrations. Granular sludge also showed a rapid increase in turbidity and decrease in diameter in accordance with sulfide concentration during the long-term shaking, suggesting that the strength of the granules was reduced with high-concentration sulfide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Fewer studies, however, have addressed the ultimate fate of granular biofilms. Moreover, several studies have reported the spontaneous disintegration of granular biofilms, ultimately leading to process failure (McHugh et al, 2006;Baloch et al, 2008;Kobayashi et al, 2015). Studies into development and fate of granules could help prevent or mitigate such phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies, however, have addressed the ultimate fate of granular biofilms. Moreover, several studies have reported the spontaneous disintegration of granular biofilms, ultimately leading to process failure (McHugh et al, 2006;Baloch et al, 2008;Kobayashi et al, 2015). Studies into development and fate of granules could help prevent or mitigate such phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). The most widely accepted theory states that granulation starts with a formation of a future granule’s core, comprised of filamentous methanogenic bacteria Methanothrix , together with Methanosarcina , which secrete extracellular polymers (ECP) [ 5 7 ]. The surface charge of this core changes and become attractive for the oppositely charged anaerobic bacteria that are present in the dispersed inoculum of a UASB rector [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the observed increase in their removal could be attributed to the enhanced hydrophobic interaction between these two compounds and sludge with SO4 2increase in the influent. Indeed, as discussed above, it has been reported that high SO4 2concentration could increase the release of EPS and thus enhance the hydrophobicity of anaerobic sludge (Kobayashi et al, 2015). Most hydrophilic TrOCs belong to the third group, which showed an initial decrease and then increase in the removal by AnMBR with continuous increase in the influent SO4 2concentration.…”
Section: Membrane Foulingmentioning
confidence: 75%
“…On the other hand, the residual concentrations of carazolol, amitriptyline, and hydroxyzine in the sludge phase increased with SO4 2addition. This result could be attributed to the change of biomass characteristics, for example, surface charge and hydrophobicity, caused by an enhanced release of EPS with sulphur addition (Kobayashi et al, 2015).…”
Section: Troc Adsorption On Sludgementioning
confidence: 99%